A positive electrode aluminum foil of a thermal expansion carbonized type flame-retardant safety primer, a positive electrode sheet, and a lithium battery
Patent Information
- Application Number
- CN202611528885.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-30
- Publication Date
- 2026-11-03
AI Technical Summary
Existing lithium-ion batteries suffer from thermal runaway due to internal short circuits caused by aluminum foil burrs under mechanical abuse conditions such as needle puncture. Furthermore, existing safety undercoating solutions suffer from excessively thick coatings that affect energy density, delayed passive flame retardant response, and insufficient long-term stability.
The thermally expanding and carbonizing flame-retardant safety primer coating contains expansion-carbonizing dual-function composite particles, boron nitride powder, graphene oxide, and hollow glass microspheres. Through chemical bonds, the expansion and carbonization functions are integrated to form a thermal insulation-thermal conduction-carbonization enhancement functional chain, achieving rapid response and effectively preventing thermal runaway.
Without affecting the normal electrochemical performance of the battery, it effectively blocks internal short circuits, improves abuse safety, maintains battery energy density and cycle life, and has long-term electrolyte tolerance and fast-response safety protection capabilities.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of secondary battery technology, specifically relating to a positive electrode aluminum foil with a thermal expansion carbonization type flame retardant safety base coating, a positive electrode sheet, and a lithium battery. Background Technology
[0002] Lithium-ion batteries are widely used in electric vehicles and energy storage systems due to their high energy density and long cycle life, but their safety remains a key bottleneck restricting their further large-scale application. Among various abuse conditions, internal short circuits caused by needle puncture are considered one of the most dangerous factors leading to battery thermal runaway. When a metal needle punctures the battery separator, sharp metal burrs are generated at the break point of the positive electrode aluminum foil current collector. These burrs directly penetrate the negative electrode and form a local short circuit with the negative electrode material, instantly generating a large amount of Joule heat. This triggers a series of chain exothermic reactions, such as the decomposition of the positive electrode material and the combustion of the electrolyte, ultimately leading to battery fire or even explosion. How to effectively block internal short circuits and interrupt the thermal runaway chain reaction under extreme abuse conditions such as needle puncture has become a core problem that urgently needs to be solved in the field of lithium-ion battery safety research.
[0003] To address the aforementioned issues, researchers have explored various technical approaches. At the current collector level, in the paper "Thermoexpandable Microsphere-Coated Al Foil Current Collector for Lithium-Ion Batteries with Improved Safety," Pengfei Lv et al. proposed pre-coating a protective layer of thermally expandable microspheres and conductive carbon black onto the surface of an aluminum foil current collector. This utilizes the volume expansion of the thermally expandable microspheres at high temperatures to block electron transport channels, thereby preventing thermal runaway in the battery during nail penetration experiments. While this approach demonstrates the feasibility of using thermal expansion mechanisms to improve nail penetration safety, its mechanism relies solely on the physical expansion blocking electron channels, failing to form an effective thermal insulation layer while simultaneously blocking conductivity. Furthermore, the introduction of conductive carbon black may increase the electron conduction path of the coating at room temperature, potentially impacting the accuracy of safety protection. Regarding flame-retardant undercoatings, Chinese patent application CN119480902A discloses a positive electrode sheet with a flame-retardant conductive undercoating on the current collector surface, using aluminum hydroxide as the flame retardant. This solution achieves flame retardancy by absorbing heat and releasing water vapor through the thermal decomposition of aluminum hydroxide. However, aluminum hydroxide has a high thermal decomposition temperature and the decomposition process is irreversible. Its flame retardant effect is a passive response type, making it difficult to provide effective protection within the extremely short time window of needle penetration. In addition, existing base coating solutions generally suffer from problems such as excessive coating thickness leading to battery energy density loss and decreased stability after prolonged contact between the coating and the electrolyte.
[0004] Therefore, there is an urgent need for a new type of positive electrode current collector safety undercoating technology that can remain thin and light at room temperature without affecting the normal electrochemical performance of the battery, and can actively and quickly respond when the local high temperature is caused by needle penetration. This technology can effectively block internal short circuits and suppress thermal runaway chain reactions when the battery is subjected to mechanical abuse, while also having good electrolyte tolerance and long-term cycle stability. Summary of the Invention
[0005] The purpose of this invention is to provide a positive electrode aluminum foil, positive electrode sheet, and lithium battery with a thermally expanding carbonized flame-retardant safety undercoating. This invention aims to solve the technical problem of thermal runaway caused by internal short circuits due to aluminum foil burrs under mechanical abuse conditions such as needle puncture in existing lithium-ion batteries. At the same time, it overcomes the defects of existing safety undercoating solutions, such as excessive coating thickness affecting energy density, delayed passive flame retardant response, and insufficient long-term stability. Thus, it significantly improves the abuse safety of the battery without sacrificing the normal electrochemical performance of the battery.
[0006] To achieve the above objectives, the present invention provides the following technical solution: The first aspect of this invention provides a positive electrode aluminum foil with a thermally expanding carbonized flame-retardant safety primer coating, comprising an aluminum foil substrate and a thermally expanding carbonized flame-retardant safety primer coating disposed on at least one surface of the aluminum foil substrate, wherein the thermally expanding carbonized flame-retardant safety primer coating comprises the following components: 45-60 parts of expanded-carbonized bifunctional composite particles, 12-18 parts of hollow glass microspheres, 5-10 parts of boron nitride powder, 0.5-2 parts of graphene oxide, 12-18 parts of polyamide-imide, and 0.8-1.2 parts of polyvinylpyrrolidone. The expanded-carbonized bifunctional composite particles are composite particles with phosphorus-containing and nitrogen-containing groups grafted onto the surface of expandable graphite.
[0007] Furthermore, the preparation method of the expanded-carbonized bifunctional composite particles includes the following steps: (1) Disperse expandable graphite in a mixed solution of concentrated sulfuric acid and potassium permanganate, stir and react at 0~5℃ for 2~4 hours, and obtain activated expandable graphite after terminating the reaction, washing and drying. (2) Activated expandable graphite is dispersed in an organic solvent, and trimethylolpropane phosphite and 4-dimethylaminopyridine are added. The mixture is stirred at 60~100℃ for 6~12 hours. After washing and drying, phosphorus-grafted expandable graphite is obtained. (3) Disperse phosphorus-grafted expandable graphite in an organic solvent, add melamine, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, stir and react at 50~80℃ for 8~16 hours, and obtain the expanded-carbonized bifunctional composite particles after washing and drying.
[0008] Further, in step (1), the mass ratio of expandable graphite to concentrated sulfuric acid is 1:5 to 1:15, and the mass ratio of potassium permanganate to expandable graphite is 1:2 to 1:5.
[0009] Further, in step (2), the mass ratio of trimethylolpropane phosphite to activated expandable graphite is 1:2 to 1:5, and the mass ratio of 4-dimethylaminopyridine to activated expandable graphite is 1:20 to 1:50.
[0010] Further, in step (3), the mass ratio of melamine to phosphorus-grafted expandable graphite is 1:2 to 1:4, the mass ratio of N,N'-dicyclohexylcarbodiimide to phosphorus-grafted expandable graphite is 1:5 to 1:10, and the mass ratio of N-hydroxysuccinimide to phosphorus-grafted expandable graphite is 1:10 to 1:20.
[0011] At room temperature, the composite particles of this invention are simply ordinary solid powders, no different from conventional fillers, neither conducting electricity nor participating in electrochemical reactions. After a localized short circuit is induced by needle puncture, the temperature rises to the expansion threshold of expandable graphite. The intercalation material between the layers decomposes to produce gas, pushing the graphite layers apart along the c-axis, causing rapid volume expansion. This expansion significantly increases the particle surface area. The phosphorus-containing groups originally encapsulated on the particle surface are exposed to the high-temperature environment and decompose to produce phosphoric acid. This phosphoric acid directly acts on adjacent graphite carbon layers, catalyzing their carbonization and cross-linking. Simultaneously, nitrogen-containing groups decompose to release gas, forming a porous structure in the carbonized layer, preventing the carbon layer from becoming too dense and brittle. The expansion and carbonization occur sequentially—expansion opens the interlayer channels first, followed by carbonization to fix and strengthen the expanded carbon layer—but both occur within the same particle, completed in situ by chemically bonded phosphorus and nitrogen groups. In traditional physical mixing schemes, the expansion component and the carbonization component are independently dispersed in the coating. When heated, expansion occurs on particle A and carbonization occurs on particle B. Whether the two can work together effectively depends on the mixing uniformity. However, this invention integrates the two functions into the same particle through chemical bonds, ensuring the spatial identity and temporal continuity of expansion and carbonization. This difference determines that a precise and rapid in-situ response can be achieved under the local high temperature at the moment of needle puncture.
[0012] Furthermore, the single-sided coating weight of the thermally expanding carbonized flame-retardant safety primer is 3~8 g / m². 2 .
[0013] Furthermore, the thermally expanded carbonized flame-retardant safety primer is prepared by the following method: expanding-carbonized bifunctional composite particles, hollow glass microspheres, boron nitride powder, graphene oxide, polyamide imide and polyvinylpyrrolidone are dispersed in an organic solvent to form a slurry, the slurry is coated on the surface of an aluminum foil substrate and dried to obtain the final product; the solid content of the slurry is 10%~30%, and the organic solvent is N-methylpyrrolidone.
[0014] Furthermore, the mass ratio of the hollow glass microspheres, boron nitride powder, and graphene oxide is (14~16):(6~8):1.
[0015] At the moment of needle puncture, a large amount of heat is generated locally at the puncture point. The hollow glass microspheres trap the heat at the puncture point in the vertical direction, preventing it from spreading into the battery. Boron nitride spreads the heat along the coating plane, preventing excessive concentration of hot spots. However, the boron nitride particles are discretely distributed in the coating, separated from adjacent particles by low thermal conductivity binder regions. This results in discontinuous heat conduction pathways in the planar direction, requiring heat to repeatedly cross low thermal conductivity interfaces during inter-particle transfer, weakening the thermal diffusion efficiency of boron nitride. The two-dimensional sheet structure of graphene oxide can be spread between boron nitride particles, acting as a thermal bridge connecting isolated boron nitride particles to form a continuous planar thermal conduction network. Simultaneously, graphene oxide is reduced at high temperatures, further enhancing its thermal conductivity during heating. This reduction temperature range matches the expansion trigger temperature of expandable graphite, allowing the in-situ strengthening of the thermal conduction network and expansion carbonization to start simultaneously. Furthermore, the sheet structure of graphene oxide can reflect some thermal radiation and participate in carbonization at high temperatures, increasing the density of the carbon layer. Hollow glass microspheres, boron nitride, and graphene oxide work together to form a complete functional chain of thermal insulation, thermal conductivity, and carbonization enhancement.
[0016] A second aspect of the present invention provides a positive electrode sheet, comprising a positive electrode aluminum foil with a thermally expanding carbonized flame-retardant safety primer coating as described in the present invention and a positive electrode active material layer disposed on the surface of the thermally expanding carbonized flame-retardant safety primer coating.
[0017] A third aspect of the present invention provides a lithium battery comprising the positive electrode, negative electrode, separator, and non-aqueous electrolyte described in the present invention.
[0018] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: This invention provides a cathode aluminum foil undercoating solution that combines active safety response with long-term electrochemical compatibility. The undercoating does not increase the battery's internal resistance at room temperature, nor does it affect the normal charge-discharge behavior of the cathode active material layer, solving the problem of traditional safety coatings sacrificing basic battery performance due to excessive thickness or poor conductivity. When a needle puncture causes localized high temperatures, the undercoating rapidly expands and carbonizes, physically encapsulating the burrs on the punctured aluminum foil, fundamentally cutting off short-circuit pathways. This solves the industry problem of ternary lithium batteries failing needle penetration tests. Phosphorus and nitrogen-containing groups on the surface of the composite particles are chemically bonded, ensuring that the active components do not dissolve or migrate during electrolyte immersion and long-term charge-discharge. Furthermore, the combination of heat-insulating and heat-conducting units in the undercoating allows the coating to both block heat from spreading inwards and dissipate heat in a timely manner when dealing with localized thermal shocks, avoiding the risk of single heat-insulating materials failing due to localized overheating. This characteristic of being inert at room temperature and actively responding under abuse conditions enables the battery to achieve reliable safety protection capabilities without sacrificing energy density and cycle life. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Unless otherwise specified, all raw materials used in the embodiments are commercially available products. The following sources are illustrative examples.
[0021] The hollow glass microspheres were purchased from 3M, model 3M. TM S35; hexagonal boron nitride powder was purchased from Qingzhou Fangzhou New Materials Co., Ltd.; polyamide-imide was purchased from Kaiyin Chemical, model Solvay / Syensqo Torlon® AI-30; expandable graphite was purchased from Nanjing Muke Nanotechnology Co., Ltd.
[0022] Example 1 This embodiment provides a positive electrode aluminum foil with a thermally expanding carbonized flame-retardant safety primer coating. The following components are weighed in parts by weight: 55 parts of expanded-carbonized bifunctional composite particles, 16 parts of hollow glass microspheres, 8 parts of hexagonal boron nitride powder, 1 part of graphene oxide, 15 parts of polyamide-imide (content 35%) in solids, and 1 part of polyvinylpyrrolidone. The above components are added to N-methylpyrrolidone, stirred and dispersed evenly, and the solid content is adjusted to 20% to obtain the primer coating slurry.
[0023] The above-mentioned slurry was coated onto one side of the aluminum foil substrate using a gravure coating method. The coating speed was 20 m / min, the drying temperature was 120℃, and the coating amount on one side was 5 g / m. 2 After drying, a positive electrode aluminum foil with a thermally expanded carbonized flame-retardant safety base coating is obtained.
[0024] The expanded-carbonized bifunctional composite particles were prepared according to the following method: (1) Add 50 g of expandable graphite to 500 g of concentrated sulfuric acid (98% by mass), add 20 g of potassium permanganate while stirring, control the reaction temperature at 3℃, and stir for 3 hours. After the reaction is completed, slowly pour the product into deionized water to terminate the reaction, filter, wash repeatedly with deionized water until the pH of the filtrate is neutral, and vacuum dry at 80℃ for 12 hours to obtain activated expandable graphite.
[0025] (2) 30 g of activated expandable graphite was dispersed in 500 mL of N,N-dimethylformamide, 10 g of trimethylolpropane phosphite and 1 g of 4-dimethylaminopyridine were added, and the mixture was stirred at 80 °C for 9 hours. After the reaction was completed, the mixture was filtered, washed successively with N,N-dimethylformamide and anhydrous ethanol, and dried under vacuum at 80 °C for 12 hours to obtain phosphorus-grafted expandable graphite.
[0026] (3) 20 g of phosphorus-grafted expandable graphite was dispersed in 400 mL of N,N-dimethylformamide, and 8 g of melamine, 3 g of N,N'-dicyclohexylcarbodiimide and 1.2 g of N-hydroxysuccinimide were added. The mixture was stirred at 65 °C for 12 hours. After the reaction was completed, the mixture was filtered and washed successively with N,N-dimethylformamide and anhydrous ethanol. The mixture was then dried under vacuum at 80 °C for 12 hours to obtain expanded-carbonized bifunctional composite particles.
[0027] Example 2 This embodiment provides a positive electrode aluminum foil with a thermally expanding carbonized flame-retardant safety primer coating. The following components are weighed in parts by weight: 52 parts of expanded-carbonized bifunctional composite particles, 16 parts of hollow glass microspheres, 7 parts of hexagonal boron nitride powder, 1 part of graphene oxide, 17 parts of polyamide-imide (content 35%) in solids, and 0.9 parts of polyvinylpyrrolidone. The above components are added to N-methylpyrrolidone, stirred and dispersed evenly, and the solid content is adjusted to 25% to obtain the primer coating slurry.
[0028] The above-mentioned slurry was coated onto one side of an aluminum foil substrate using a gravure coating method. The coating speed was 15 m / min, the drying temperature was 110℃, and the coating amount on one side was 4 g / m. 2 After drying, a positive electrode aluminum foil with a thermally expanded carbonized flame-retardant safety base coating is obtained.
[0029] The expanded-carbonized bifunctional composite particles were prepared according to the following method: (1) Add 50 g of expandable graphite to 600 g of concentrated sulfuric acid (98% by mass), add 15 g of potassium permanganate while stirring, control the reaction temperature at 2℃, and stir for 3.5 hours. After the reaction is completed, slowly pour the product into deionized water to terminate the reaction, filter, wash repeatedly with deionized water until the pH of the filtrate is neutral, and vacuum dry at 80℃ for 12 hours to obtain activated expandable graphite.
[0030] (2) 30 g of activated expandable graphite was dispersed in 500 mL of N,N-dimethylformamide, 8 g of trimethylolpropane phosphite and 1.2 g of 4-dimethylaminopyridine were added, and the mixture was stirred at 90 °C for 8 hours. After the reaction was completed, the mixture was filtered, washed successively with N,N-dimethylformamide and anhydrous ethanol, and dried under vacuum at 80 °C for 12 hours to obtain phosphorus-grafted expandable graphite.
[0031] (3) 20 g of phosphorus-grafted expandable graphite was dispersed in 400 mL of N,N-dimethylformamide, and 6 g of melamine, 2.5 g of N,N'-dicyclohexylcarbodiimide and 1.5 g of N-hydroxysuccinimide were added. The mixture was stirred at 70 °C for 10 hours. After the reaction was completed, the mixture was filtered and washed successively with N,N-dimethylformamide and anhydrous ethanol. The mixture was then dried under vacuum at 80 °C for 12 hours to obtain expandable-carbonized bifunctional composite particles.
[0032] Example 3 This embodiment provides a positive electrode aluminum foil with a thermally expanding carbonized flame-retardant safety primer coating. The following components are weighed in parts by weight: 58 parts of expanded-carbonized bifunctional composite particles, 18 parts of hollow glass microspheres, 6 parts of hexagonal boron nitride powder, 1.5 parts of graphene oxide, 14 parts of polyamide-imide (content 35%) in solids, and 1.1 parts of polyvinylpyrrolidone. The above components are added to N-methylpyrrolidone, stirred and dispersed evenly, and the solid content is adjusted to 15% to obtain the primer coating slurry.
[0033] The above-mentioned slurry was coated onto one side of an aluminum foil substrate using a gravure coating method at a coating speed of 25 m / min and a drying temperature of 130℃. The coating amount on one side was 6.5 g / m. 2 After drying, a positive electrode aluminum foil with a thermally expanded carbonized flame-retardant safety base coating is obtained.
[0034] The expanded-carbonized bifunctional composite particles were prepared according to the following method: (1) Add 50 g of expandable graphite to 450 g of concentrated sulfuric acid (98% by mass), add 22 g of potassium permanganate while stirring, control the reaction temperature at 4℃, and stir for 2.5 hours. After the reaction is completed, slowly pour the product into deionized water to terminate the reaction, filter, wash repeatedly with deionized water until the pH of the filtrate is neutral, and vacuum dry at 80℃ for 12 hours to obtain activated expandable graphite.
[0035] (2) 30 g of activated expandable graphite was dispersed in 500 mL of N,N-dimethylformamide, 12 g of trimethylolpropane phosphite and 0.8 g of 4-dimethylaminopyridine were added, and the mixture was stirred at 70 °C for 11 hours. After the reaction was completed, the mixture was filtered, washed successively with N,N-dimethylformamide and anhydrous ethanol, and dried under vacuum at 80 °C for 12 hours to obtain phosphorus-grafted expandable graphite.
[0036] (3) 20 g of phosphorus-grafted expandable graphite was dispersed in 400 mL of N,N-dimethylformamide, and 9 g of melamine, 3.5 g of N,N'-dicyclohexylcarbodiimide and 1 g of N-hydroxysuccinimide were added. The mixture was stirred at 60 °C for 14 hours. After the reaction was completed, the mixture was filtered and washed successively with N,N-dimethylformamide and anhydrous ethanol. The mixture was then dried under vacuum at 80 °C for 12 hours to obtain expandable-carbonized bifunctional composite particles.
[0037] Comparative Example 1 The difference between this comparative example and Example 1 is that the expanded-carbonized bifunctional composite particles were prepared according to the following method: (1) Add 50 g of expandable graphite to 500 g of concentrated sulfuric acid (98% by mass), add 20 g of potassium permanganate while stirring, control the reaction temperature at 3℃, and stir for 3 hours. After the reaction is completed, slowly pour the product into deionized water to terminate the reaction, filter, wash repeatedly with deionized water until the pH of the filtrate is neutral, and vacuum dry at 80℃ for 12 hours to obtain activated expandable graphite.
[0038] (2) 30 g of activated expandable graphite was dispersed in 500 mL of N,N-dimethylformamide, 10 g of phosphorus oxychloride and 5 g of triethylamine were added, and the mixture was stirred at 60 °C for 9 hours under nitrogen protection. After the reaction was completed, the mixture was filtered, washed successively with N,N-dimethylformamide and anhydrous ethanol, and dried under vacuum at 80 °C for 12 hours to obtain phosphorus-grafted expandable graphite.
[0039] (3) 20 g of phosphorus-grafted expandable graphite was dispersed in 400 mL of N,N-dimethylformamide, and 8 g of melamine, 3 g of N,N'-dicyclohexylcarbodiimide and 1.2 g of N-hydroxysuccinimide were added. The mixture was stirred at 65 °C for 12 hours. After the reaction was completed, the mixture was filtered and washed successively with N,N-dimethylformamide and anhydrous ethanol. The mixture was then dried under vacuum at 80 °C for 12 hours to obtain the expanded-carbonized bifunctional composite particles.
[0040] Everything else is the same as in Example 1.
[0041] Comparative Example 2 The difference between this comparative example and Example 1 is that the expanded-carbonized bifunctional composite particles were prepared according to the following method: (1) Add 50 g of expandable graphite to 500 g of concentrated sulfuric acid (98% by mass), add 20 g of potassium permanganate while stirring, control the reaction temperature at 3℃, and stir for 3 hours. After the reaction is completed, slowly pour the product into deionized water to terminate the reaction, filter, wash repeatedly with deionized water until the pH of the filtrate is neutral, and vacuum dry at 80℃ for 12 hours to obtain activated expandable graphite.
[0042] (2) 30 g of activated expandable graphite was dispersed in 500 mL of N,N-dimethylformamide, 10 g of trimethylolpropane phosphite and 1 g of 4-dimethylaminopyridine were added, and the mixture was stirred at 80 °C for 9 hours. After the reaction was completed, the mixture was filtered, washed successively with N,N-dimethylformamide and anhydrous ethanol, and dried under vacuum at 80 °C for 12 hours to obtain phosphorus-grafted expandable graphite.
[0043] (3) 20 g of phosphorus-grafted expandable graphite was dispersed in 400 mL of N,N-dimethylformamide, and 8 g of ethylenediamine, 3 g of N,N'-dicyclohexylcarbodiimide and 1.2 g of N-hydroxysuccinimide were added. The mixture was stirred at 65 °C for 12 hours. After the reaction was completed, the mixture was filtered and washed successively with N,N-dimethylformamide and anhydrous ethanol. The mixture was then dried under vacuum at 80 °C for 12 hours to obtain the expanded-carbonized bifunctional composite particles.
[0044] Everything else is the same as in Example 1.
[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that the expanded-carbonized bifunctional composite particles were prepared according to the following method: The expanded-carbonized bifunctional composite particles are replaced with expandable graphite encapsulated in phosphorus-containing polyurethane microcapsules, and the preparation method is as follows: (1) Dissolve 10 g of tris(hydroxymethyl)phosphorus oxide in 100 mL of N,N-dimethylformamide, add 50 g of expandable graphite, and stir until homogeneous.
[0046] (2) Under stirring conditions, slowly add 20 g of N,N-dimethylformamide solution of toluene-2,4-diisocyanate (50 mL) and 0.15 g of dibutyltin dilaurate, and keep the reaction at 80°C for 8 hours.
[0047] (3) After the reaction was completed, the sample was filtered and washed repeatedly with N,N-dimethylformamide and anhydrous ethanol. The sample was then dried under vacuum at 80°C for 12 hours to obtain expandable graphite coated with phosphorus-containing polyurethane microcapsules.
[0048] Everything else is the same as in Example 1.
[0049] Comparative Example 4 The difference between this comparative example and Example 1 is as follows: The base coating slurry is made by weighing the following components in parts by weight: 56 parts of expanded-carbonized bifunctional composite particles, 16 parts of hollow glass microspheres, 8 parts of hexagonal boron nitride powder, 15 parts of polyamide-imide (content 35%) in solids, and 1 part of polyvinylpyrrolidone; the above components are added to N-methylpyrrolidone, stirred and dispersed evenly, and the solid content is adjusted to 20% to obtain the base coating slurry.
[0050] Everything else is the same as in Example 1.
[0051] Comparative Example 5 The difference between this comparative example and Example 1 is as follows: The base coating slurry is made by weighing the following components in parts by weight: 50 parts of expanded-carbonized bifunctional composite particles, 10 parts of hollow glass microspheres, 12 parts of hexagonal boron nitride powder, 0.3 parts of graphene oxide, 15 parts of polyamide-imide (content 35%) in solids, and 1 part of polyvinylpyrrolidone; the above components are added to N-methylpyrrolidone, stirred and dispersed evenly, and the solid content is adjusted to 20% to obtain the base coating slurry.
[0052] Everything else is the same as in Example 1.
[0053] Performance testing (I) Preparation of lithium-ion batteries The positive electrode aluminum foils obtained in Examples 1-3 and Comparative Examples 1-5 were cut into the required sizes and assembled with graphite negative electrode sheets and polyethylene separators to form soft-pack cells. A non-aqueous electrolyte of 1 mol / L LiPF6 ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) (volume ratio 1:1:1) was injected, and after formation and capacity testing, lithium-ion batteries with a rated capacity of 5 Ah were produced. Ten batteries from each example and comparative example were tested, and the average value was taken.
[0054] (II) Testing Methods: 1. Needle prick test The battery was tested according to the needle penetration test method in section 6.2.8 of GB / T 31485-2015 "Safety Requirements and Test Methods for Power Batteries for Electric Vehicles". After the battery was fully charged according to the standard, a high-temperature resistant steel needle with a diameter of 5 mm (needle tip cone angle of 45°~60°) was used to penetrate the battery from a direction perpendicular to the battery plates at a speed of (25±5) mm / s. After penetration, the steel needle remained in place for at least 1 hour to observe whether the battery caught fire or exploded. The number of batteries that did not catch fire or explode in each group of 10 batteries was recorded, and the pass rate (%) was calculated.
[0055] 2. Cyclic life test The test was conducted in accordance with GB / T 31484-2015, "Cycle Life Requirements and Test Methods for Power Batteries for Electric Vehicles". The initial capacity of each battery was determined at room temperature according to Clause 6.2 of the standard. Charge-discharge cycles were performed at an ambient temperature of 25±2℃ using a 1C / 1C current density, and the number of cycles required for the battery capacity to decay to 80% of its initial capacity was recorded.
[0056] 3. DC internal resistance test Referring to the FreedomCAR HPPC test procedure, the DC internal resistance of the battery was tested using the hybrid pulse power characteristic method. The battery was discharged at 1C to 50% state of charge, left to stand for 1 hour, and then discharged at 4C for 10 seconds. The voltage difference before and after discharge was recorded, and the DC internal resistance was calculated using the formula DCIR = ΔU / I.
[0057] 4. Coating adhesion test after electrolyte immersion The positive electrode aluminum foil sample coated with the primer was immersed in a non-aqueous electrolyte of 1 mol / L LiPF6 in ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) (volume ratio 1:1:1) at 60℃ for 30 days, and then removed. After the sample was placed in an environment of 23±2℃ and 50±5% relative humidity for 24 hours, the coating adhesion was tested according to GB / T 9286-2021 "Cross-cut Test for Paints and Varnishes". Depending on the thickness of the primer (1.5~4 μm), a 1 mm spacing blade was used to make a cross-cut, and the sample was then covered with 3M 600 tape and peeled off. The adhesion grade was recorded (grade 0 is the best, grade 5 is the worst).
[0058] The test results are shown in Table 1.
[0059] Table 1 Performance Test Results sample Acupuncture success rate (%) Cycle life (times, capacity retention 80%) DC internal resistance DCIR (mΩ) Adhesion (grade) after immersion in electrolyte Example 1 100 1846 1.8 0 Example 2 100 1773 1.9 0 Example 3 80 1612 2.1 0 Comparative Example 1 60 1338 2.5 0 Comparative Example 2 50 1276 2.4 0 Comparative Example 3 40 1115 2.8 3 Comparative Example 4 60 1407 2.1 0 Comparative Example 5 30 1072 3.2 0 The performance test results above show that the tests in Examples 1-3 demonstrate that the technical solution of the present invention does not affect the normal electrochemical performance of the battery at room temperature, effectively blocks thermal runaway when local high temperatures are induced by needle penetration, and the coating adhesion does not decrease after immersion in electrolyte. The base coating exhibits long-term stability in the electrolyte environment. In Examples 1 and 2, because the mass ratio of hollow glass microspheres, boron nitride powder, and graphene oxide is controlled within a specific range, the needle penetration pass rate reaches 100%, indicating that strictly controlling the ratio of the three components can achieve better safety protection.
[0060] Comparative Example 1 used phosphorus oxychloride as the phosphorus source. Its excessively high reactivity led to uneven grafting of phosphorus-containing groups onto the expandable graphite surface, resulting in asynchronous carbonization reactions during expansion and the inability to form an effective carbon layer in some areas, thus causing unstable needle-punching protection. Comparative Example 2 used ethylenediamine as the nitrogen source. Its aliphatic structure released significantly less nitrogen gas at high temperatures than the triazine ring structure of melamine, resulting in insufficient foaming and an undesirable pore structure in the carbonized layer, leading to inadequate heat insulation and blocking effects. Comparative Example 3 used physical coating instead of chemical bonding grafting. The lack of chemical bonds between the phosphorus-containing polyurethane layer and the expandable graphite caused the coating to gradually detach after prolonged immersion in the electrolyte, resulting in the loss of active components and a decline in safety performance. Comparative Example 4 lacked graphene oxide. The boron nitride particles could not form a continuous thermally conductive network, and heat could only be transferred through random contact between the boron nitride particles, which was far less efficient than when graphene oxide bridging was used. Local hot spots could not be dissipated in time during needle puncture. In Comparative Example 5, the insufficient amount of hollow glass microspheres resulted in an inadequate vertical thermal insulation barrier, while the excessive amount of boron nitride introduced heat into the coating. The insufficient amount of graphene oxide failed to effectively bridge the boron nitride particles to form a continuous thermally conductive network, ultimately leading to a significant reduction in the needle penetration protection effect.
[0061] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A positive electrode aluminum foil with a thermally expanding, carbonizing, flame-retardant, and safe primer coating, characterized in that, The material includes an aluminum foil substrate and a thermally expandable, charred, flame-retardant, and safe primer coating disposed on at least one surface of the aluminum foil substrate. By weight, the thermally expandable, charred, flame-retardant, and safe primer coating comprises the following components: 45-60 parts of expanded-carbonized bifunctional composite particles, 12-18 parts of hollow glass microspheres, 5-10 parts of boron nitride powder, 0.5-2 parts of graphene oxide, 12-18 parts of polyamide-imide, and 0.8-1.2 parts of polyvinylpyrrolidone. The preparation method of expanded-carbonized bifunctional composite particles includes the following steps: (1) Disperse expandable graphite in a mixed solution of concentrated sulfuric acid and potassium permanganate, stir and react at 0~5℃ for 2~4 hours, and obtain activated expandable graphite after terminating the reaction, washing and drying. (2) Activated expandable graphite is dispersed in an organic solvent, and trimethylolpropane phosphite and 4-dimethylaminopyridine are added. The mixture is stirred at 60~100℃ for 6~12 hours. After washing and drying, phosphorus-grafted expandable graphite is obtained. (3) Disperse phosphorus-grafted expandable graphite in an organic solvent, add melamine, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, stir and react at 50~80℃ for 8~16 hours, and obtain the expanded-carbonized bifunctional composite particles after washing and drying.
2. The positive electrode aluminum foil with a thermally expanding, carbonized, flame-retardant, and safe primer coating according to claim 1, characterized in that, The mass ratio of expandable graphite to concentrated sulfuric acid in step (1) is 1:5 to 1:15, and the mass ratio of potassium permanganate to expandable graphite is 1:2 to 1:
5.
3. The positive electrode aluminum foil with a thermally expanding, carbonized, flame-retardant, and safe primer coating according to claim 1, characterized in that, In step (2), the mass ratio of trimethylolpropane phosphite to activated expandable graphite is 1:2 to 1:5, and the mass ratio of 4-dimethylaminopyridine to activated expandable graphite is 1:20 to 1:
50.
4. The positive electrode aluminum foil with a thermally expanding, carbonized, flame-retardant, and safe primer coating according to claim 1, characterized in that, In step (3), the mass ratio of melamine to phosphorus-grafted expandable graphite is 1:2 to 1:4, the mass ratio of N,N'-dicyclohexylcarbodiimide to phosphorus-grafted expandable graphite is 1:5 to 1:10, and the mass ratio of N-hydroxysuccinimide to phosphorus-grafted expandable graphite is 1:10 to 1:
20.
5. The positive electrode aluminum foil with a thermally expanding, carbonized, flame-retardant, and safe primer coating according to claim 1, characterized in that, The single-sided coating weight of the thermally expanding carbonized flame-retardant safety primer is 3~8 g / m². 2 .
6. The positive electrode aluminum foil with a thermally expanding, carbonized, flame-retardant, and safe primer coating according to claim 1, characterized in that, The thermally expandable carbonized flame-retardant safety primer is prepared by the following method: expanding-carbonized bifunctional composite particles, hollow glass microspheres, boron nitride powder, graphene oxide, polyamide imide and polyvinylpyrrolidone are dispersed in an organic solvent to form a slurry, the slurry is coated on the surface of an aluminum foil substrate and dried to obtain the primer; the solid content of the slurry is 10%~30%, and the organic solvent is N-methylpyrrolidone.
7. The positive electrode aluminum foil with a thermally expanding, carbonized, flame-retardant, and safe primer coating according to claim 1, characterized in that, The mass ratio of the hollow glass microspheres, boron nitride powder, and graphene oxide is (14~16):(6~8):
1.
8. A positive electrode sheet, comprising a positive electrode aluminum foil with a thermally expanding carbonized flame-retardant safety primer coating as described in any one of claims 1-7 and a positive electrode active material layer disposed on the surface of the thermally expanding carbonized flame-retardant safety primer coating.
9. A lithium battery comprising the positive electrode sheet as described in claim 8, a negative electrode sheet, a separator, and a non-aqueous electrolyte.
Citation Information
Patent Citations
Positive plate, lithium ion battery and positive plate preparation method
CN119480902A
